SYNTHESIS OF 5-BENZIMIDAZOLYLBENZOFURAN DERIVATIVES OF EXPECTED BIOLOGICAL ACTIVITY - A.ElHag, Fatma AbdAleem; ElHarbi, Reem A.K.; Edress, Fatma M.; El Diwani, Hoda I. (European Scientific Journal, ESJ, 2013)
The benzimidazole starting material 5-(1H-benzo[d]imidazol-2-yl)-4,7-dimethoxybenzofuran- 6-ol (2)was synthesized. The Mannich bases 3a-k were formed using formaldehyde and primary or secondary amines.(2) was subjected to Mannich reaction using 1,4-phenylenediamine or piperazine to lead to the 1,4-disubstituted benzenes 4a or 1,4-disubstituted piperazines 4b. The compounds were screen for their antimicrobial activities